2020
DOI: 10.21203/rs.3.rs-87485/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Probiotic Alleviate Fluoride-Induced Memory Impairment by Reconstructing Gut Microbiota in Mice

Abstract: BackgroundFluoride which is widespread in our environment and food due to geological origin and industrial pollution has been identified as developmental neurotoxicants. Gut-brain axis provide new sight to the brain-derived injury. We hypothesized that fluoride-induced memory impairment was associated with gut dysbiosis, which could be prevented by improving the gut microbiota. MethodsMice were given fluoridated drinking water (sodium fluoride, 100 mg/L) for 70 days and administered with PBS or a probiotic str… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Used qPCR to determine the relative expression abundance between IL-1b, IL-6, IL-10, IFN-g, TNF-a and the internal reference gene b-actin in small intestine (34). The primer sequences used for qPCR are shown in Supplementary Table S3.…”
Section: Quantitative Real-time Pcr Detection Of Cytokine Expression ...mentioning
confidence: 99%
“…Used qPCR to determine the relative expression abundance between IL-1b, IL-6, IL-10, IFN-g, TNF-a and the internal reference gene b-actin in small intestine (34). The primer sequences used for qPCR are shown in Supplementary Table S3.…”
Section: Quantitative Real-time Pcr Detection Of Cytokine Expression ...mentioning
confidence: 99%
“…As shown in Table 2, many studies have reported the beneficial effects of probiotics on neurological disorders and gut microbiota. A previous study showed that L. johnsonii BS15 intake can improve intestinal inflammation, neuroinflammation, and fluorine-induced and restraint stress-induced memory dysfunction by improving inflammation and permeability (Xin et al, 2020;Wang et al, 2021). In addition, L. johnsonii CJLJ103 was able to alleviate colitis and memory impairment by inhibiting NF-jB activation and intestinal lipopolysaccharide production (Lim et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…We isolated Lactobacillus johnsonii YH1136 (CCTCC M 20221116) from feces of a healthy Tibetan girl in Baingoin county, the Nagqu region of the Tibet Autonomous Region, at an altitude of 5000 meters. Based on our previous studies, Lactobacillus johnsonii shows promising results by improving intestinal microbiota in preventing and treating nonalcoholic fatty liver disease, modulating stress and memory impairment based on the gutbrain axis, and plays an important regulatory role in processes involved in renal and intestinal injury induced by high fluoride exposure (10,(14)(15)(16)(17)(18)(19). Therefore, this study evaluated whether L.johnsonii YH1136 is effective in mitigating damage to intestinal integrity due to hypoxic environments in rats exposed to high altitudes.…”
Section: Introductionmentioning
confidence: 99%